The Role of PAK1 in the Maturation of Invadopodia During Transient Mechanical Stimulation - Gasparski, Alexander N.; Wilson, Jacob T.; Banerjee, Anindita; Beningo, Karen A. (Frontiers in Cell and Developmental Biology, 2019)
Abstract Cancer cells are affected by a wide range of mechanical forces within their extracellular environment. It has been widely shown that these forces can lead to increased metastatic activity of these cells. One such force is a transient tugging-like force that results from contractile forces generated by cells within the tumor microenvironment. When this force is simulated in vitro with a mechano-invasion assay, human fibrosarcoma cells exhibit enhanced cell invasion in a 3D collagen-fibronectin matrix by downregulating the expression of integrin β3. Furthermore, this force stimulates the maturation of invadopodia in an integrin β3-dependent manner that includes an increase in the active form of cofilin and MMP-2 secretion. In the present study we discovered that the decrease in integrin β3 signaling in response to mechanical stimulation is coupled to the activity of p21-activated kinase 1 (PAK1). It was found that PAK1 has decreased activity, as detected by a decrease in Ser144 phosphorylation, with mechanical stimulation. However, this loss in phosphorylation can be reversed if integrin β3 is overexpressed. Furthermore, PAK1 mutants show a correlated response in MMP-2 enzyme expression and activity, in addition to the lengthening of invadopodia, in response to stimulation. These results identify a novel mechano-sensitive response in human fibrosarcoma that utilizes PAK1 as a signaling player positioned downstream of integrin β3.